FESTIVALS FOR THE DEVELOPMENT OF CRAFTSMANSHIP IN SOUTHERN UZBEKISTAN - Mamarajabov Gairat Abdulkhakimovich (Journal of Learning on History and Social Sciences, 2024)
This article provides information about the development of handicrafts in the Southern regions and the holding of handicraft festivals, their description and the training of artisans and master-apprentice issues